Mother Language Inheritance Through Language Policies, Use in The Family, School And Community - Defina - (Madah: Jurnal Bahasa dan Sastra, 2023)
The extinction of languages in the world is inevitable with globalization and regional languages in Indonesia. In this regard, the purpose of this paper is to describe the Government of Indonesia's policy towards the maintenance of regional languages; the use of regional languages in the realm of family, school, and society. This research is descriptive research with data collection techniques through library research. As a result, the government has issued many regulations governing the use of local languages and creating programs for their maintenance, starting from families and schools to the wider community. The use of the mother tongue originating from the regional language in the family sphere is mostly spoken by the older generation. Regional languages are still used in communicating among ethnic groups among the older generation but are not always spoken by the younger generation. At school teachers provide opportunities to use local languages in communication at school. In conclusion, the Government of Indonesia's policies must continue to be realized through language counseling programs, awarding regional language proficiency exam (UKBD) pass certificates, and awarding regional language activists